Inclusão digital: a acessibilidade das páginas Web dos repositórios institucionais para deficientes visuais em Portugal - Quaresma, Helena (2015)
Open Access (OA) is a movement that advocates full access to scientific information. It is not however only open access to this literature, it is also, as highlighted in the declarations of Budapest, Bethesda and Berlin, the removal of barriers to access, enhancing their reuse in new contexts or larger, both disciplinary as geographical. In Portugal, the Scientific Open Access Repository (RCAAP) was established, which has the mission to promote, support and facilitate the adoption of the OA movement and is the focal point of the Portuguese institutional repositories. This study is intended to determine the accessibility for visually impaired web pages of scientific OA repositories of Portugal. To this end, it applied the AccessMonitor to a sample of 32 Web sites (home pages) scientific repositories of open access included in RCAAP. The AccessMonitor is an automatic validator provided by the Foundation for Science and Technology of Portugal, which checks the application of the accessibility guidelines in the HTML of a Web site and using as a reference to version 2.0 of the Accessibility Guidelines for Web Content Content (WCAG 2.0) of the W3C, but allows also the Web page validation according to standard WCAG1.0